Play-Based Contextual Learning for Pre-Reading Development in Preschoolers with ADHD Risk Factors - Astuti, Juni Nuri; Mahabbati, Aini (Journal of Innovation and Research in Primary Education, 2025)
Children at risk for ADHD frequently experience difficulties in developing pre-reading skills due to challenges with attention regulation and executive function. This study investigated the effectiveness of play-based contextual learning methods in enhancing pre-reading abilities among preschool children exhibiting ADHD risk characteristics. A classroom action research design following the Kemmis and McTaggart model was implemented over two cycles with two children (aged 5-6 years) identified as at risk for ADHD at State Kindergarten 2 Kaubun. The intervention integrated Contextual Teaching and Learning (CTL) principles through play-based activities using familiar materials (vegetables) to teach letter recognition, phonemic awareness, and word formation. Data collection employed pre-reading ability assessments, structured observations, and documentation of behavioral changes across baseline, Cycle 1, and Cycle 2 phases. Substantial improvements were observed from baseline to final assessment: Subject AY progressed from 27.77% to 83.33%, while Subject AL advanced from 30.55% to 88.88% proficiency. Both participants exceeded the 75% threshold for independent skill demonstration. Qualitative observations revealed enhanced attention regulation, increased engagement, and improved self-regulation behaviors throughout the intervention period. The findings demonstrate that culturally responsive, multisensory play-based approaches effectively address both cognitive and behavioral domains in children at risk for ADHD. The intervention's success supports the integration of constructivist learning principles with inclusive educational practices, providing evidence for combined treatment approaches addressing reading difficulties and attention challenges simultaneously.